2011
DOI: 10.1007/s12035-011-8210-4
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the PKC Signaling System in the Pathophysiology and Treatment of Mood Disorders: Involvement of a Functional Imbalance?

Abstract: Mood disorders, such as bipolar and major depressive disorders, are frequent, severe, and often disabling neuropsychiatric diseases affecting millions of individuals worldwide. Available mood stabilizers and antidepressants remain unsatisfactory because of their delayed and partial therapeutic efficacy. Therefore, the development of targeted therapies, working more rapidly and being fully effective, is urgently needed. In this context, the protein kinase C (PKC) signaling system, which regulates multiple neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 101 publications
1
26
0
Order By: Relevance
“…All PKC isozymes are highly expressed in the central nervous system, mainly in brain regions involved in mood regulation (Abrial et al, 2011). Some studies showed that prefrontal cortex post-mortem tissue samples from suicide victims with a history of a diagnosis of depression had a decreased activity of PKC (Pandey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All PKC isozymes are highly expressed in the central nervous system, mainly in brain regions involved in mood regulation (Abrial et al, 2011). Some studies showed that prefrontal cortex post-mortem tissue samples from suicide victims with a history of a diagnosis of depression had a decreased activity of PKC (Pandey et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…PKC, a main regulator of the phospholipase C/Ca 2+ system, plays an important role in cell signal transduction (21). Through the PKC/CREB signaling pathway, PKC regulates the excitability of nerve cells and affects the synthesis and release of monoamine neurotransmitters, with a relatively high content in the hippocampus (22).…”
Section: Discussionmentioning
confidence: 99%
“…912 PKCα, the most predominant isoenzyme in mouse, 13 rabbit, 14 and human 15 hearts, has been identified as a major regulator of heart contractility, 15,16 platelet aggregation in thrombosis, 1719 and virtually every development stage of atherosclerotic disease. 20,21 Up-regulation of PKCα has been demonstrated in breast cancer cells, 22,23 melanoma cells, 24 and tissue samples of urinary bladder carcinomas 25 and malignant gliomas.…”
Section: Introductionmentioning
confidence: 99%